Highly aligned hierarchical intrafibrillar mineralization of collagen induced by periodic fluid shear stress - Du, Tianming; Niu, Xufeng; Hou, Sen; Xu, Menghan; Li, Zhengwei; Li, Ping; Fan, Yubo (Journal of materials chemistry. B, Materials for biology and medicine, 2020)
Periodic fluid shear stress (FSS) is one of the main mechanical microenvironments in mineralization of bone matrix. To elucidate the mechanism of periodic FSS in collagen mineralization, a mechanical loading induced mineralization system is developed and compared with traditional polyacrylic acid (PAA) induced mineralization. Fourier transform infrared (FTIR) spectroscopy, calcium-to-phosphorus molar ratio and transmission electron microscopy (TEM) demonstrate that both periodic FSS and PAA can control the size of amorphous calcium phosphate (ACP) to avoid aggregation and help the formation of intrafibrillar mineralization. Differently, periodic FSS under a proper cycle and range can accelerate the conversion of ACP to apatite crystals and alleviate the reduced transformation caused by PAA. Under the action of template analogues, periodic FSS can also promote the formation of highly oriented hierarchical intrafibrillar mineralized (HIM) collagen. These findings are helpful for understanding the mechanism of collagen mineralization in natural bone matrix and contribute to the design of novel bone substitute materials with hierarchical structures. Periodic fluid shear stress plays a dominant role in promoting the preparation of highly oriented HIM of collagen fibers.